Determinants of Sukuk Issuers’ Financial Stability : Evidence from Malaysia - Xiaoting, Chen; Nurul Izza, Abd Malek; Abu Hassan, Md. Isa; Muhamad Abdullah, Zaidel (UNIMAS PUBLISHER, 2021)
Financial stability and Sukuk expanded swiftly into the financial industry after the 2007-2008 global financial turmoil. Malaysia's Sukuk market is arguably the most prominent in Islamic finance globally, and its inherent nature gives it a better security on the premise of guaranteed firms’ financial stability and returns to investors. This study aims to explore the extent of the Malaysian firms’ financial stability are being influenced by the characteristics of Sukuk and also the firms’ characteristics. Sixty-one listed companies that have issued Sukuk from 1997 to 2017 have been selected for this study. The nai ̈ve distance to default (DD) developed by Bharath and Shumway was used as a measure of the firms’ financial stability. Ordinary Least Squares (OLS) was employed in this study, and the results confirmed that Sukuk could promote the firms’ financial stability. The variables related to the characteristics of Sukuk that were found to influence financial stability were the intensity of Sukuk and the proportion of Sukuk financing. The firm size, valuation, solvency, and profitability were the firms’ characteristics that have also affected the firms’ financial stability significantly. All these provide evidences that Malaysia should play more active role in promoting the development of Sukuk market, and at the same time should be aware that financial stability is a systematic element which involved many complex factors.